Protecting ITER walls: fast ion power loads in 3D magnetic field. (18th October 2016) - Kurki-Suonio, T; Särkimäki, K; Äkäslompolo, S; Varje, J; Liu, Y; Sipilä, S; Asunta, O; Hirvijoki, E; Snicker, A; Terävä, J; Cavinato, M; Gagliardi, M; et al.
Abstract: The fusion alpha and beam ion with steady-state power loads in all four main operating scenarios of ITER have been evaluated by the ASCOT code. For this purpose, high-fidelity magnetic backgrounds were reconstructed, taking into account even the internal structure of the ferritic inserts and tritium breeding modules (TBM). The beam ions were found to be almost perfectly confined in all scenarios, and only the so-called hybrid scenario featured alpha loads reaching 0.5 MW due to its more triangular plasma. The TBMs were not found to jeopardize the alpha confinement, nor cause any hot spots. Including plasma response did not bring dramatic changes to the load. The ELM control coils (ECC) were simulated in the baseline scenario and found to seriously deteriorate even the beam confinement. However, the edge perturbation in this case is so large that the sources have to be re-evaluated with plasma profiles that take into account the ECC perturbation.